English Job Interview Analysis in the Hospitality Industry: Human Resource Professionals’ Prefer-ences - Putu Ayu Prabawati Sudana; Made Aryawan Adijaya (Balai Bahasa Provinsi Bali, 2026)
A job interview is a significant factor in the recruiting and selection process, particularly in the hospitality sector, where English is widely spoken. Despite their importance, there are only a few empirical research works dedicated to English job interviews in the hospitality environment. This study aims to examine the nature of job interviews in the hospitality industry based on human resource (HR) practitioners in terms of interview preparation, interview types, interview type questions, evaluation of the candidates, and interview etiquette. A qualitative research strategy was employed with 20 HR professionals in Bali through a validated questionnaire and semi-structured interviews. The findings show structured interviews are the most preferred type of interviews, followed by unstructured and behavioural interviews, respectively. Some of the most significant measured competencies are problem-solving, leadership, interpersonal, adaptability, and personal qualities. In addition to that, HR professionals emphasize professional interview etiquette, which involves punctuality, good appearance, attitude, and honesty. This study concludes that interviews are to be combined with other selection methods, which will lead to a more profound assessment of the applicants. These findings are applicable to the English for Specific Purposes (ESP), particularly in developing English job interview instructional materials for hospitality students.AbstrakWawancara kerja merupakan faktor penting dalam proses rekrutmen dan seleksi, terutama di sektor hospitality di mana bahasa Inggris banyak digunakan. Meskipun penting, hanya sedikit penelitian empiris yang fokus pada wawancara kerja dalam bahasa Inggris di lingkungan perhotelan. Studi ini bertujuan untuk menganalisis wawancara kerja di industri perhotelan berdasarkan persepsi praktisi sumber daya manusia (SDM) dalam hal persiapan wawancara, jenis wawancara, pertanyaan dalam wawancara, evaluasi calon, dan etika wawancara. Strategi penelitian kualitatif diterapkan dengan melibatkan 20 profesional SDM di Bali melalui kuesioner yang telah tervalidasi dan wawancara semi-terstruktur. Temuan menunjukkan bahwa wawancara terstruktur adalah jenis wawancara yang paling disukai, diikuti oleh wawancara tidak terstruktur dan wawancara perilaku. Beberapa kompetensi yang paling signifikan yang diukur meliputi pemecahan masalah, kepemimpinan, interpersonal, adaptabilitas, dan kualitas pribadi. Selain itu, praktisi SDM menekankan etika wawancara profesional, yang meliputi ketepatan waktu, penampilan yang baik, sikap, dan kejujuran. Studi ini menyimpulkan bahwa wawancara harus dikombinasikan dengan metode seleksi lain, yang akan menghasilkan penilaian yang lebih mendalam terhadap calon karyawan. Temuan ini berlaku untuk Bahasa Inggris untuk Tujuan Khusus (ESP), khususnya dalam pengembangan materi instruksional wawancara kerja dalam bahasa Inggris untuk mahasiswa perhotelan.